Altering an appreciative system: Lessons from incorporating dual-use concerns into the responsible science education of biotechnologists. (April 2019) - Novossiolova, Tatyana; Whitman, Jim; Dando, Malcolm
Highlights: The concept of an appreciative system is an important analytical tool for understanding professional cultures. Education and awareness-raising are essential but not sufficient prerequisites for changing an appreciative system. Effective education requires both interdisciplinary courses and active learning teaching and training methods. Abstract: The broad and continuing applicability of Geoffrey Vickers' work owes much to his concern with the human condition in changed and changing circumstances. An important instance of this problem is the relationship between the potential of scientific advances which can greatly enhance human well-being but also find application in new or enhanced weapons of mass destruction. Clearly, preventing such weapons from becoming a normal part of conflict during a period of rapid scientific and technological change in the sciences will require an integrated system of laws and regulations implementing the international agreements. Yet it will also require that the scientific community, through their daily practice and norms of professional conduct, support the efforts to maintain and further develop relevant international treaties that seek to limit the spread of and outlaw such weapons. The purpose of this paper therefore is to examine the utility of Vickers' concept of an Appreciative System for developing a systematic theoretical framework for understanding what change mechanism is efficacious in the education of scientists regarding the extent to which new ideas about ethics and professional responsibility can be grasped, acknowledged and applied.